A new species of Xenylla Tullberg, 1869 (Collembola: Hypogastruridae) from China, with a key to Asian species of the genus - Jia, Junli; Skarżyński, Dariusz (Zootaxa, 2019)
A new species of the genus Xenylla Tullberg, 1869 is described. The new species, Xenylla weinerae sp. nov., from China, resembles X. acauda Gisin, 1947, X. brevicauda Tullberg, 1869, X. caudata Jordana, 1993, X. lesnei Denis, 1935, X. nirae Gama & Oliveira, 1994, X. wandae Queiroz & Mendonça, 2016 and X. vanharteni Weiner et al., 2012 due to unique feature––six thickened cylindrical sensilla on antennal segment IV. X. weinerae sp. nov. having moderately modified chaetotaxy (b h1 h2 q t, head with dorsal setae l1 and l3 subequal, dorsal setae a3 on Abd. IV present) and well-developed furca (mucro separated from the dens, bearing 2 setae) is also similar to some populations of X. obscura Imms, 1912 sensu Thibaud et al. (2004). An identification key to Asian Xenylla species is provided.